Effects of curing period on iodine-fortified salted chicken egg - Lugo, Maria Teresa Baclaan (2006.)
The study was conducted using a fixed -effects one-factor experiment in a completely randomized desgn to determine the effects of curing period on iodine-fortified salted chicken egg (IFSCE).
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Curing; Salted chicken egg; Iodine fortified